The Prophet Yunus (Alayhi As-Salam) being swallowed by a Big Fish: A Spiritual View in the Light of Current Information - HÜSEYIN ÇAKSEN (Pakistan Journal of Medical & Health Sciences, 2025)
Prophets are highly qualified individuals who are tasked with conveying the information and commands they receive through revelation from Allah and calling their interlocutors to the true religion. One-hundred and twenty-four thousand prophets came from the first Prophet Adam (Alayhi As-Salam [AS]), the first man, to the last Prophet Muhammad (Sallallahu Alayhi Wa Sallam). A total of 25 prophets’ names has been mentioned in the Quran and one of them is the Prophet Yunus (AS), also known as Jonas or Jonah. Moreover, the tenth Surah including 109 ayats of the Quran is the Surah Yunus. Yunus Ibn Matta (Jonah son of Amittai or Jonas) lived during of the reign of the second Jeroboam (793-753 BC), one of the kings of Israel. It was stated in the holy books including the Bible, the Hebrew Bible (Tanakh) and the Quran that the Prophet Yunus (AS) was swallowed by a big fish and then he was saved by the will of Allah. However, some authors claimed that the story of Jonah was a myth, fable, or symbolic story3,4. Herein, we discuss the story of Yunus (AS) being swallowed by a big fish in light of current information to emphasize that Yunus’s (AS) story is not a myth and that it contains some lessons for today’s people including scientists.